Why cumulative loading calculated using non-weighted integration may not be suitable for assessing physical stress of the lower back: an empirical investigation of strain during lifting and lowering tasks. Issue 1 (2nd January 2022) - Johnen, Laura; Mertens, Alexander; Nitsch, Verena; Brandl, Christopher
Abstract: When work-related physical stress is assessed using non-weighted integration, it is assumed that different loading conditions have a sufficiently comparable effect on the human body as long as the area under the loading curve is the same. Growing evidence cast doubt on whether this simple calculation can adequately estimate physical work-related strain. This study investigates in vivo, focussing on the lower back, whether the non-weighted method adequately reflects work-related physical strain of the lower back. Strain data resulting from lifting/lowering tasks performed in a laboratory study with an identical area under the loading curve but different load intensities were compared. Results showed that the non-weighted method does not sufficiently reflect the resulting muscular, cardiovascular and perceived strain but underestimates the influence of higher load intensity even in the range of medium physical exposure. Further research is needed regarding the determination of weighting factors and limit values. Practitioner Summary Given the dynamic nature of most physical work activities, the assessment of time-varying loading of the lower back is of particular interest in practice. Results show that the widely used non-weighted calculation method does not accurately reflect the resulting physical strain but underestimates the influence of higher load intensity. Abbreviations: MSD: musculoskeletal disorders; WMSD: work-related musculoskeletal disorders; KIM-LHC: Key Indicator Method Lifting, Holding, Carrying; RES: right erector spinae longissimus; LES: left erector spinae longissimus; HR: heart rate; RPE: rating of perceived exertion; EMG: surface electromyography; ECG: electrocardiography; SENIAM: Surface ElectroMyoGraphy for the Non-Invasive Assessment of Muscles; MVC: maximum voluntary contraction; ANOVA: analysis of variance; Std. error: standard error HIGHLIGHTS: Results of this empirical investigation suggest that the widely used non-weighted calculation method is not fully suitable for calculating cumulative loading of the lower back. Even in the range of medium physical exposure the non-weighted calculation method does not accurately reflect the resulting strain on the human body but tends to underestimate the influence of higher load intensity due to higher external weight. Despite the same cumulative loading value obtained when using the non-weighted method, the resulting physical strain values are generally about 20–25% higher. The results may be used to further develop ergonomic assessment methods in order to avoid a misclassification of loading conditions and to prevent the risk of overexertion.